(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, we use contraction mapping principle and operator-theoretic approach to establish local solvability of the elliptic-parabolic (hyperbolic) Type Chemotaxis System. In addition, global solvability of the systems is considered by some uniform estimates.